Contagion effects of financial crisis: a meta-analysis - Mohamad, Azhar (s.n, 2015)
During the last two decades, the phenomenon of financial contagion has been investigated in numerous pieces of research using various methodologies. Indeed, financial contagion has severe implications for the stability of domestic financial systems as well as offering diversification benefits due to international portfolio investment. Given the devastating effects of the Global Financial Crisis on world financial markets, stock markets across the world could encounter financial contagion. Thus, our current study has been designed to provide an overview of the evidence of financial contagion in global financial markets pertaining to the Global Financial Crisis. In particular, we have collected, classified and synthesized the extant literature in the Scopus database on our topic of concern. We hope the findings of our research will assist the policy makers and portfolio investors realize the vulnerability of their national stock markets to the contagion effect of external financial turbulence. In addition, these findings should provide direction for future research on the financial contagion effect.